Disengaging Whiteness and Examining Power in Campus Activism: Reuniting Communities of Color Through a Critical Race Analysis of Tempered Radicalism - Veronica A. Jones; Dian Squire (Journal Committed to Social Change on Race and Ethnicity, 2018)
This manuscript provides a nuanced understanding of the heterogeneity of faculty and staff of color activism in the context of a racialized and racist university structure. Through the deployment of Critical Race Theory, and the couching of activism within a foundational white supremacist history of higher education, the authors are then able to repair discord between students who often see faculty and staff of color as complacent within their institutions. These critiques often do not take into consideration how racism constricts faculty and staff of color action and also comes with classist assumptions via an insinuation that all faculty and staff of color can risk loss of job as a result of activism. Moreover, an intersectional lens is not always considered in activism literature. At the same time, the authors argued that faculty and staff of color, particularly those who identify as Black, must be allowed to act in untempered ways as their livelihoods quite literally depend on changing a broader racist system.